Critical conditions for tight oil charging and delineation of effective oil source rocks in Lucaogou Formation, Jimusar Sag, Junggar Basin, northwest China. Issue 2 (17th February 2016) - Zhou, L.; Pang, X.; Wu, L.; Kuang, L.; Jiang, F.; Pang, H.; Peng, J.; Yu, R.
ABSTRACT: Although tight oil has great resource potential, studies of oil charging mechanisms in tight reservoirs are relatively few. Researchers have found that a force balance exists during oil charging, but quantitative analyses of conditions critical for tight oil charging are sparse. This study developed a formula to identify effective source rocks using oil expulsion intensity as the discrimination parameter based on quantitative expression of hydrocarbon-generation overpressure and force-balance conditions. Using this formula, critical oil expulsion intensity under conditions at various burial depths can be obtained. This method was applied in the tight reservoirs of the Jimusar Sag, Junggar Basin, China. The calculated critical oil expulsion intensity range was between 122.61 × 10 4 t/km 2 and 620.01 × 10 4 t/km 2 . The distribution range of effective oil source rocks and total expelled oil can be determined on the basis of critical oil expulsion intensity at different burial depths. This method provides a new approach to predict favourable tight oil-bearing regions.